1996
DOI: 10.1021/ja960274f
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Inhibition of Human α-1,3-Fucosyltransferase V

Abstract: Human R-1,3-fucosyltransferase V (FucT V), which catalyzes the transfer of L-fucose moiety from guanosine diphosphate -L-fucose (GDP-Fuc) to an acceptor sugar to form sialyl Lewis x (sLe x ), was shown to proceed through an ordered, sequential mechanism by product inhibition studies. The designed azatrisaccharide propyl 2-acetamido- (2), prepared by covalently linking the N-group of -L-homofuconojirimycin (1) to the 3-OH of LacNAc through an ethylene unit, in the presence of GDP was found to be an effective in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
67
0
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 119 publications
(72 citation statements)
references
References 70 publications
4
67
0
1
Order By: Relevance
“…Similarly, it has been shown that -1,4-galactosyltransferase has a secondary isotope effect (D V ) 1.21, D V/K ) 1.05) (Kim et al, 1988) and that uridine 5′-diphospho-2-deoxy-2-fluoro-R-D-galactose is a competitive inhibitor of this enzyme (Hayashi et al, 1996). The proposed transition-state structure of FucT V is also supported by the observation that aza sugars which mimic the charge distribution of the glycosyl cation are inhibitors of FucT V, and synergistic inhibition by the combination of an aza sugar, GDP, and the acceptor sugar to mimic the transition-state structure has been illustrated (Ichikawa et al, 1992a;Murray et al, 1996;Qiao et al, 1996).…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…Similarly, it has been shown that -1,4-galactosyltransferase has a secondary isotope effect (D V ) 1.21, D V/K ) 1.05) (Kim et al, 1988) and that uridine 5′-diphospho-2-deoxy-2-fluoro-R-D-galactose is a competitive inhibitor of this enzyme (Hayashi et al, 1996). The proposed transition-state structure of FucT V is also supported by the observation that aza sugars which mimic the charge distribution of the glycosyl cation are inhibitors of FucT V, and synergistic inhibition by the combination of an aza sugar, GDP, and the acceptor sugar to mimic the transition-state structure has been illustrated (Ichikawa et al, 1992a;Murray et al, 1996;Qiao et al, 1996).…”
mentioning
confidence: 70%
“…Similarly, it has been shown that -1,4-galactosyltransferase has a secondary isotope effect (D V ) 1.21, D V/K ) 1.05) (Kim et al, 1988) and that uridine 5′-diphospho-2-deoxy-2-fluoro-R-D-galactose is a competitive inhibitor of this enzyme (Hayashi et al, 1996). The proposed transition-state structure of FucT V is also supported by the observation that aza sugars which mimic the charge distribution of the glycosyl cation are inhibitors of FucT V, and synergistic inhibition by the combination of an aza sugar, GDP, and the acceptor sugar to mimic the transition-state structure has been illustrated (Ichikawa et al, 1992a;Murray et al, 1996;Qiao et al, 1996).With the discovery of many fucosyltransferases, the limiting step in the study of these important enzymes is the synthesis of GDP-Fuc and analogs. Unlike other sugar nucleotides, the enzymatic preparation of GDP-Fuc has not been established on a large scale, and as such, several groups have reported the chemical synthesis of this substrate (Adelhorst & Whitesides, 1993; Arlt & Hindsgaul 1995; † This work was partially supported by the NIH (GM 44154), the NSF, Cytel Corporation (San Diego, CA), and the Deutsche Forschungsgemeinschaft (fellowship for V.W.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…After the formation of the new glycosidic bond, the oligosaccharide product is released first followed by the release of the nucleotide portion of the donor and eventually the flexible loops return to their original conformation to start a new catalytic cycle (43). Product inhibition studies for human FucT V suggest that this enzyme also follows an ordered sequential bi-bi mechanism (49), and it is likely that the H. pylori FucTs do the same. It is tempting to speculate that the hypervariable loop of H. pylori FucTs corresponds to a similar flexible active site loop that interacts with both donor and acceptor substrates.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wong and co-workers prepared β-L-homofuconojirimycin (β-HFJ) 12 by an aldolase-based strategy. 41 The acceptor substrate (±)-threo-azidoaldehyde 82 was synthesized from commercially available 2-butyn-1-al diethyl acetal 81 (Scheme 16). Aldolase catalyzed aldol condensation of 82 with dihydroxyacetone phosphate (DHAP) followed by dephosphorylation with acid phosphatase afforded the desired enantiomerically pure azidoketose 83.…”
Section: (Vi) Enzyme Catalyzed Intramolecular Reductive Amination Strmentioning
confidence: 99%